2011
DOI: 10.4161/cib.17138
|View full text |Cite
|
Sign up to set email alerts
|

C. elegansmodel of neuronal aging

Abstract: Aging of the nervous system underlies the behavioral and cognitive decline associated with senescence. Understanding the molecular and cellular basis of neuronal aging will therefore contribute to the development of effective treatments for aging and age-associated neurodegenerative disorders. Despite this pressing need, there are surprisingly few animal models that aim at recapitulating neuronal aging in a physiological context. We recently developed a C. elegans model of neuronal aging, and showed that age-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The progressive loss of neuronal integrity in csb-1 mutants was characterized by an early-onset of increased beading that precedes axonal degeneration. We also detected aberrant neurite morphology, bubble-like lesions (bridging) and neurite sprouting (branching) along the axons of mechanosensory neurons; features that naturally appear during advanced age in the C. elegans neuronal system ( 20 ). Neuronal maintenance in ageing is governed by the Jun kinase (JNK-1) and insulin signalling via DAF-16/FOXO ( 20 , 46 , 47 ), both of which have been implicated in the DNA damage response (DDR; ( 15 , 48 ).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The progressive loss of neuronal integrity in csb-1 mutants was characterized by an early-onset of increased beading that precedes axonal degeneration. We also detected aberrant neurite morphology, bubble-like lesions (bridging) and neurite sprouting (branching) along the axons of mechanosensory neurons; features that naturally appear during advanced age in the C. elegans neuronal system ( 20 ). Neuronal maintenance in ageing is governed by the Jun kinase (JNK-1) and insulin signalling via DAF-16/FOXO ( 20 , 46 , 47 ), both of which have been implicated in the DNA damage response (DDR; ( 15 , 48 ).…”
Section: Discussionmentioning
confidence: 83%
“…We also detected aberrant neurite morphology, bubble-like lesions (bridging) and neurite sprouting (branching) along the axons of mechanosensory neurons; features that naturally appear during advanced age in the C. elegans neuronal system ( 20 ). Neuronal maintenance in ageing is governed by the Jun kinase (JNK-1) and insulin signalling via DAF-16/FOXO ( 20 , 46 , 47 ), both of which have been implicated in the DNA damage response (DDR; ( 15 , 48 ). We previously showed that the activation of the transcription factor DAF-16 upon UV-induced DNA damage promotes developmental growth and lifespan in csb-1 mutants thus counteracting the consequences of unrepaired DNA damage ( 13 , 15 ).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Several aspects involved in aging and longevity have been studied in this model organism, such as DNA damage, mitochondrial dysfunction, autophagy impairment, and nutrient sensing dysregulation 11,12 . Some efforts have also been devoted to explore neurodegeneration induced by aging, as C. elegans is also very important in neuroscience studies, mainly due to its fully mapped neuronal connections 11,1318 . Aging induces phenotypes reminiscent of functional deterioration in the nervous system: motility decline, long-term associative memory deterioration, and changes in neuronal morphology and synaptic patterning 14,15,1719 .…”
Section: Introductionmentioning
confidence: 99%